Formulation of Komba-Komba Leaf Extract Ointment (Chromolaena odorata L) for Wound Healing - Satria, Beny Maulana; Zulfahrin, LM Zulfahrin; Sopian, Ahmad (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Wounds are physical injuries that can cause damage to skin tissue. The extract of komba-komba leaves (Chromolaena odorata L) contains flavonoids, saponins, and tannins, which are wound healers formulated as ointment preparations. This study aims to determine how administering komba-komba leaf extract ointment affects wound healing. The maceration method obtained a thick extract of komba-komba leaves. Komba-komba leaf extract ointment was made in three formulas based on differences in extract concentration: FI = 5%, FII = 10% and FIII = 15%). The ointment preparations obtained were subjected to organoleptic tests (color, odor, and consistency) and physical tests, including homogeneity, pH, viscosity, spreadability, stability tests, and scratch wound healing activity tests. The results showed that the extract’s concentration affected the ointment preparation's color, consistency, and physical properties. The effectiveness test results for healing scratches showed that the ointment preparation with an extract concentration of 15% provided an effective healing speed.